PENGARUH SUBTITUSI TEPUNG DAUN KELOR (Moringa oleifera Lam.) TERHADAP SIFAT ORGANOLEPTIK DAN KADAR KALSIUM SNACK BAR - Nur Fahlia (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
The application of moringa leaves flour is finite. This research aims to analyze the substitution effect of Moringa leaves flour on snack bars. This experimental research design uses a Completely Randomized Design (CRD) with three substitution levels including F1 (95% wheat flour and 5% Moringa leaves flour), F2 (90% wheat flour and 10% Moringa leaves flour) and F3 (85% wheat flour and 15% moringa leaves flour). Data from organoleptic test results were analyzed using the ANOVA test if there are significant differences followed by Duncan's further tests. While the results of proximate levels and calcium levels were analyzed using an independent t-test. The organoleptic analysis of the hedonic test showed that the selected snack bar formula was F2. The result of proximate analysis of selected snack bars contains 12.52% water, 1.65% ash, 19.61% fat, 9.23% protein, 56.99% carbohydrate, and 344.14 mg /100g calcium. The contribution of selected snack bar energy is 441.37 kcal per 100 grams and 203.03 kcal per serving size (46 gram). This research concludes that proximate levels in the form of water, ash, fat, protein, carbohydrate have significant differences (p <0.05) in each analysis. Selected calcium snack bar levels have high calcium claims.